2014
DOI: 10.1167/iovs.14-15464
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics of the Infant Aphakia Treatment Study Population: Predicting Recognition Acuity at 4.5 Years of Age

Abstract: This analysis concurs with previous studies that early surgery is important for good visual outcomes in patients with unilateral infantile cataracts. The fact that only one baseline variable (private insurance) contributed to the multivariate analysis, accounting for 12% of the variance, suggests that predicting visual outcome for these patients is complicated at best, and cannot be estimated from baseline characteristics alone. (ClinicalTrials.gov number, NCT00212134.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 18 publications
2
19
0
1
Order By: Relevance
“…Evaluation of the relationship between visual acuity at 4.5 years of age and age at surgery in IATS (28–48 vs. 49–210 days at surgery) revealed median visual acuity was significantly better for eyes operated younger vs. older (0.50 versus 1.10 logMAR, p=0.046). 31 Therefore, the desire to achieve maximum visual acuity must be counterbalanced against an increased risk of glaucoma or glaucoma suspect diagnosis in an infant with a unilateral congenital cataract.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the relationship between visual acuity at 4.5 years of age and age at surgery in IATS (28–48 vs. 49–210 days at surgery) revealed median visual acuity was significantly better for eyes operated younger vs. older (0.50 versus 1.10 logMAR, p=0.046). 31 Therefore, the desire to achieve maximum visual acuity must be counterbalanced against an increased risk of glaucoma or glaucoma suspect diagnosis in an infant with a unilateral congenital cataract.…”
Section: Discussionmentioning
confidence: 99%
“…In the Infant Aphakia Treatment Study (IATS), we found that socioeconomic status, measured by the availability of private insurance, and greater amounts of patching were the best predictors of a good visual acuity outcome. 7,8 However, neither variable accounted for 415% of the variance in visual outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…Visual outcomes are often disappointing. Younger age at surgery is associated with better visual outcomes 5,6 . Unilateral cases have a worse visual prognosis in the affected eye than bilateral: at six years after surgery, a median visual acuity 0.48 in bilateral and 1.0 logMAR (affected eye) in unilateral cases has been reported 3 .…”
Section: Introductionmentioning
confidence: 99%